Kansei Engineering in Designing Web-Based e-Commerce UMKM Product - Isa, Indra Griha Tofik; Ariyanti, Indri (JOIN (Jurnal Online Informatika), 2021)
Human-Computer Interaction (HCI) is a part of the development of a system in addition to the usability factor. Several methods were developed in HCI to produce a User Interface design that persuasively attracts the user’s interest. One of these methods was Kansei Engineering which involved psychological factors and user emotions in the stage. The study focused on developing the e-commerce User Interface for UMKM products which based on how to maximize the service and quality of e-Commerce because so far the development of the web-based UMKM  e-Commerce product user interface has not paid attention to psychological factors. The Research followed Kansei Engineering Type 1 (KEPack) with the stages: (1) Research Initiation, (2) Collecting Kansei Words (KW), (3) Translating KW into SD scale, (4) Collecting Specimens, (5) Classifying Item / Category Specimens, (6) Evaluating Questionnaire Participants’ Data, (7) Multivariate Statistical Analysis, (8) Translating Statistical Data into Design Elements, (9) Creating Guideline Matrix Kansei Engineering. This study involved 40 participants, 20 Kansei Words, and ten specimens of UMKM e-Commerce products. The final result is the Kansei e-Commerce matrix guideline for web-based UMKM products, which had two main concepts, they were complexity consisting of formal, natural and simple emotion factors; and Uniqueness consisting of Comfortable, Soft, and Unique which consists of 8 main parts which divided into 65 design elements. The contribution of this Research in the informatics area is to provide recommendations for the appearance of  web-based UMKM  e-Commerce products based on the psychological factors of the user through the Kansei Engineering Stages.